Trade Openness, Growth and Income Inequality: Case of Tunisia, an ARDL and PMG/ARDL Approach - BEN YOUNES, Hamza; BEN AMEUR, Fayçal (European Journal of Science, Innovation and Technology, 2024)
Trade openness has long been a major topic of debate, mainly because of the countless effects it can have on countries, particularly in terms of growth and wealth. While some see it as an efficient catalyst for growth, others claim that it contributes to the polarization of wealth without generating inclusive economic growth, resulting in the marginalization of the poorest social classes. For the Tunisian case, our analysis using an ARDL model as well as a PMG/ARDL model, allowed us to conclude that trade openness has a positive effect on economic growth. We were also able to detect a negative effect on wage inequalities within the various sectors that constitute the Tunisian economy, in line with the predictions of the traditional theories on the impact of trade openness in developing countries.